Shaping Arctic’s tomorrow through Indigenous knowledge engagement and knowledge co-production - Degai, Tatiana; Petrov, Andrey N; Badhe, Renuka; Egede Dahl, Parnuna P; Döring, Nina; Dudeck, Stephan; Herrmann, Thora M; Golovnev, Andrei; Mack, Liza; Omma, Elle Merete; Retter, Gunn-Britt; Saxinger, Gertrude; et al. (Sustainability, 2022)
This perspective presents a statement of the 10th International Congress of Arctic Social Sciences Indigenous Knowledge and knowledge co-production panel and discussion group, 20 July 2021. The statement is designed to serve as a characterization of the state-of-the-art and guidance for further advancement of Indigenous Knowledge and knowledge co-production in the Arctic. It identifies existing challenges and provides specific recommendations for researchers, Indigenous communities, and funding agencies on meaningful recognition and engagement of Indigenous Knowledge systems. This research was funded by the US National Science Foundation, grant number 2001989. Faculty Reviewed